2006
DOI: 10.1002/14651858.cd003087.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Double gloving to reduce surgical cross-infection

Abstract: Analysis 3.1. Comparison 3 Single gloves versus indicator systems-proportion of perforations detected during surgery, Outcome 1 Proportion of perforations detected during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 102 publications
1
96
1
13
Order By: Relevance
“…With more specimens, more detailed analysis of risk by glove type and other factors could be possible. Double gloving is an effective way to protect patients and practitioners and is common practice in our institution; however, double gloving, while common, is not universally practiced [7,13,18]. Mischke et al [13] found inner-glove puncture risk could be reduced by 71% with double gloving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With more specimens, more detailed analysis of risk by glove type and other factors could be possible. Double gloving is an effective way to protect patients and practitioners and is common practice in our institution; however, double gloving, while common, is not universally practiced [7,13,18]. Mischke et al [13] found inner-glove puncture risk could be reduced by 71% with double gloving.…”
Section: Discussionmentioning
confidence: 99%
“…The use of power tools, handling sharp bone, and working in deep cavities all influence the risk of glove perforations in orthopaedic surgery [20]. Double gloving has been recommended in orthopaedic procedures to ameliorate the risk of perforation but compliance is not universal [7,18]. Duration of wear, degree of soilage, and other risk factors for glove perforation also have been reported [2,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double gloving reduces the risk of glove perforation; and in procedures such as orthopaedic surgeries, where sharp edges could be encountered easily, following double gloving protocols is highly recommended (65)(66)(67). However, with a double gloving protocol, the inner glove could still be perforated and become contaminated during the course of the procedure.…”
Section: Surgical Glovesmentioning
confidence: 99%
“…99,100 Universal and standard infection control procedures are designed to protect healthcare workers and patients, 101 although compliance in dental practice is sometimes lacking. 101 Glove perforation is not uncommon, 102 but most, 103,104 though not all 105 reports support the practice of double gloving as effective.…”
Section: Generalmentioning
confidence: 99%